Penerapan Model Pembelajaran Role Playing Untuk Meningkatkan Hasil Belajar Siswa Pada Pembelajaran Tematik Kelas III SD Negeri 104201 Kolam Tahun Ajaran 2022/2023 - Khoiriyah Hasibuan, Nurul (Educate: Jurnal Ilmu Pendidikan dan Pengajaran, 2022)
The problem in this study is the low learning outcomes in thematic learning, especially theme 2 loving plants and animals, and sub-theme 2 the benefits of animals for human life. This study aimed to improve student learning outcomes by applying the Role Playing learning model to theme 2 loving plants and animals, and sub-theme 2 the benefits of animals for human life. This type of research is "Classroom Action Research". The subjects of this study were third-grade students of SD Negeri 104201 Kolam, totaling 23 students consisting of 10 male students and 13 female students, while the object of this study was student learning outcomes in thematic learning by applying the role playing learning model. This research was conducted in 2 cycles, namely cycle I and cycle II, each cycle consisting of 1 meeting, with 4 stages, namely planning, implementation, observation, and reflection. Data collection techniques used are tests, observation sheets, and documentation. What is analyzed is test data and observation data during the learning process. Based on this research, shows that student learning outcomes have increased in each cycle. In the pre-test of 23 students, 6 students finished studying with a completeness percentage of 26.09%, and students who did not complete there were 17 students with a completeness percentage of 73.91% and classified as a very poor category. Then followed up in the first cycle 12 students completed with a percentage of completeness of 52.17% and students who did not complete there were 11 students with a percentage of completeness of 47.83% belonging to the less category. Then in the second cycle, 21 students completed with a percentage of completeness of 91.30% and students who did not complete 2 students with a percentage of completeness of 8.70% and were categorized as very good. From the results of the research above, it can be concluded that student learning outcomes increase if the Role Playing learning model is applied to thematic learning theme 2 loving animals and plants sub-theme 2 the benefits of animals for human life. It is recommended that teachers also apply for the Role Playing learning model in the learning process, especially in thematic learning subjects theme 2 love animals and plants sub-theme 2 the benefits of animals for human life.